Socially Responsible Employment: Expectations of New Entrants in Hungary - Pecze, Krisztina; Polák-Weldon, Réka; Juhász, Tímea; Oravecz, Titanilla (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Ensuring high-quality labour is crucial for companies, and socially responsible employment practices play a key role in attracting and retaining talent. This study examines the preferences of new labour market entrants regarding corporate social responsibility in employment. As organizations increasingly integrate CSR strategies, understanding how these initiatives align with the values of young professionals is essential for workforce sustainability and organizational success. The research was conducted in late 2024 and early 2025 through an online survey targeting Hungarian university students studying economics and business. The study explored students’ perspectives on various socially responsible employment practices, such as benefits, hybrid work options, career development opportunities, and workplace atmosphere. Findings indicate that students prioritize a supportive work environment and meaningful internal communication. A strong positive correlation was observed between key employment practices, confirming their interdependence. Gender differences emerged, with women valuing benefits more than men. Entrepreneurial experience influenced perceptions, as those without business experience rated socially responsible employment practices as more important. These insights can help companies tailor CSR policies to better meet the expectations of young professionals, ensuring both employee satisfaction and long-term business success.